The Cultural Self-Awareness Study in the Mediated EnglishTeaching Context—A WeChat Public Account Perspective - Haiyan, Zhang (Advances in Social Sciences Research Journal, 2017)
With the increasing convergence between English teaching and the media technologies, WeChat public accounts have been broadly applied in English teaching in China. Based on the theory of Cultural Self-Awareness(CSA)and the“sixteen-Chinese-Character Philosophy”initiated by Fei Xiaotong, the founding Father of the Chinese sociology and anthropology, this paper endeavors to undertake an analysis of the content on the Chinese Spring Festival culture posted on the three selected English Learning WeChat public accounts during the Festival period, specifically, from Jan.23rdto Feb. 4th 2017. According to the data analysis of the 34 posts, findings are made that 1) None the three accounts have well practised the CSA when introducing the Spring Festival culture; 2) presenting this traditional Festival through the westerners’positive attitude is an effective and refreshing way for the Chinese youth to better understand the Chinese traditional culture; and 3) the thought-provoking explanations and resonance-arousing comments are more desired than merely offering the bilingual reading materials on the Festival to the learners.